The Effect of Traditional Jamu with Polyphenol-Rich Mixture Content on Cholesterol Levels in the Elderly with Coronary Heart Disease - Berliany Venny Sipollo; Sugiyanto; Elizabeth Yun Yun Vinsur (Babali Publisher, 2023)
Introduction: The aging process can impact the cardiovascular system in both structural and physiological ways, which can lead to atherosclerosis and an increased risk of coronary heart disease. While pharmacological interventions for CHD exist, they may come with unwanted side effects. As an alternative, many individuals turn to complementary medicine, including traditional herbal remedies. Among these remedies is a polyphenol-rich mixture (PRM) that has been shown to lower cholesterol levels and inhibit cholesterol absorption. Consequently, this study seeks to explore the efficacy of traditional herbal medicine containing PRM in reducing cholesterol levels in older adults with CHD. Methods: Design research uses quasi-experiment with two groups pre-test and post-test, the number of samples is 55 older adults with CHD, divided into 28 older adults consuming traditional herbal medicine and 27 older adults’ control. The researcher used an Accu-check to check the cholesterol level and analysed using a t-test. Results: The results showed that the decrease in mean cholesterol levels before and after the intervention period in the herbal medicine group (d = 50.50) was significantly greater than the mean score in the control group (d = -1.44) with p <.001. Conclusion: Older adults with coronary heart disease could benefit from traditional Jamu containing polyphenol-rich mixture by reducing cholesterol levels. This could be used as complementary medicine in nursing.